Akt kinase targets the association of CBP with histone H3 to regulate the acetylation of lysine K18. Issue 7 (19th February 2013) - Liu, Yan; Xing, Zhao-bin; Zhang, Jing-hua; Fang, Yue
Abstract : CBP physically interacts with AKT1 by anti tag coimmunoprecipitation (View interaction) Abstract : ► Akt regulates H3K18ac through CBP. ► CBP phosphorylation inhibits H3K18 acetylation. ► The changes in CBP substrate affinity induced by Akt are involved in signal transduction.